2022
DOI: 10.1021/acsomega.1c05542
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Detection of Fe3+ Ions Using Functionalized Graphene Quantum Dots Fabricated by a One-Step Pulsed Laser Ablation Process

Abstract: With respect to the detection of Fe3+ ions, graphene quantum dots (GQDs) have limitations for commercialization owing to their high limit of detection (LOD). Here, we report a one-step pulsed laser ablation (PLA) process to fabricate amino-functionalized GQDs (FGQDs) for the efficient detection of Fe3+ using polypyrrole (PPy) both as a precursor (amine N) and as a surfactant and also using graphite as a carbon precursor. Using this method, the amine N groups were easily incorporated into the carbon network of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…44 In a study, amino-based GQDs were made using polypyrrole (PPy) as an amine source and graphite as a carbon substrate using a one-step pulsed laser ablation (PLA) technique for the sensitive recognition of Fe3. 45 3.1.2. Arc Discharge.…”
Section: Top-down Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…44 In a study, amino-based GQDs were made using polypyrrole (PPy) as an amine source and graphite as a carbon substrate using a one-step pulsed laser ablation (PLA) technique for the sensitive recognition of Fe3. 45 3.1.2. Arc Discharge.…”
Section: Top-down Strategiesmentioning
confidence: 99%
“…By laser beam ablation in a fluid, applying pulsed graphene and adding ammonia–water to the graphene solution, nitrogen-doped GQDs were created . In a study, amino-based GQDs were made using polypyrrole (PPy) as an amine source and graphite as a carbon substrate using a one-step pulsed laser ablation (PLA) technique for the sensitive recognition of Fe3 …”
Section: Synthetic Strategies For Gqdsmentioning
confidence: 99%
“…Kang et al [ 99 ] reported the synthesis of amino-functionalized GQDs (FGQDs) for Fe 3+ sensing application, using graphite and polypyrrole (PPy) as the carbon and nitrogen precursors, respectively. Compared with pristine GQDs, FGQDs exhibited a narrow size distribution and small particle sizes due to the “surface passivation effect” of the polypyrrole surfactant.…”
Section: Key Factorsmentioning
confidence: 99%
“…However, excessive amounts of this ion can lead to poisoning and even death. Therefore, accurate and rapid determination of Fe(III) in environmental and biological samples is of great importance 1 3 .…”
Section: Introductionmentioning
confidence: 99%